Harnessing the Momentum of the Economic GIG to Increase the Transformation of the Accounting Profession in the Era of Society 5.0 - Rohmatul Faizah (Innovation Business Management and Accounting Journal, 2025)
The outbreak of economic digitalization in the era of society 5.0 and its impact has begun to be felt by various parties, including the accounting profession. There is a prediction of a decline and even the extinction of several professions in 2030 by the World Economic Forum, one of which is the accounting profession. This research is expected to provide an overview of the existence of the accounting profession, as well as the various kinds of efforts needed, as well as look at the opportunities offered to this profession in the gig economy era. The results of the study show that it is still possible for the accounting profession to survive in the era of society 5.0 until 2030, with the note that there is support from the government, namely implementing equitable distribution of digital infrastructure, to make comprehensive policies and no less crucial, namely paying attention to legal protection for workers, and in terms of workers, the readiness of human resources is needed to always adapt to various changes. Among them can be achieved by participating in education and training in accounting, taxation, and foreign language certification, improving digital capabilities, actively participating in professional communities and organizations, mastering soft skills (interpersonal and intrapersonal), and understanding applicable accounting and tax standards.